(untitled) (Vietnam Journal of Community Medicine, 2022)
Objective: This study was conducted to determine the current status and need for continuing professional training of nurses at the pediatric departments, the Hospital of Obstetrics and Gynecology, Ninh Binh Province. Methods: This is a cross-sectional study conducted on 121 subjects who are nurses from the pediatric departments at the Hospital of Obstetrics and Pediatrics, Ninh Binh province, from 7/2021 to 6/2022. The study subjects were convenient sampling. We use a self-designed set of questions. Results: In terms of training status, in 2019-2020, training courses at the Hospital have trained 100% of pediatric nurses at the hospital. The number of nurses sent for training at central level institutions accounts for a low proportion (17.36%). Compared to 2019, the number of training sessions at the Hospital will be nearly four times higher in 2020. However, the number of training sessions at central-level facilities is three times lower. Regarding training needs, out of 6 techniques in pediatrics, there are two techniques with a low proficiency level that need to be prioritized for training. In addition, there are two other techniques with medium proficiency that can be supervised training. All 17 techniques in emergency have intermediate practice proficiency. Therefore, all of these techniques have training needs at the level of supervised training. Conclusion: The results of our study show that it is advisable to focus on deploying training models with techniques with low proficiency. In addition, continuing training classes at the Hospital need to strengthen the form of practical training.